2014
DOI: 10.1016/j.jgeb.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterization of alkaline protease produced by a pink pigmented facultative methylotrophic (PPFM) strain, MSF 46

Abstract: Among the various bacterial isolates, the strain MSF 46 isolated from thorn forest soil samples, Tamil Nadu, India, was screened and characterized for its proteolytic activity. While the 16S rRNA sequencing and biochemical characterization revealed that the strain closely resembles Methylobacterium sp., methylotrophy of the strain was confirmed by the sequence homology of mxaF gene with other relative Methylobacterium sp. The alkaline protease was purified to homogeneity using DEAE cellulose ion exchange chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
(56 reference statements)
4
5
0
Order By: Relevance
“…Bacillus ruris protease had its highest activity at 50 ℃ (100%), while further temperature rise resulted in reduced protease activity decreasing to 77.042 % at 70 ℃. This result agrees with reports by (Adinarayana et al, 2003;Giri et al, 2011;Jayashree et al ., 2014;Niyonzima and More, 2014;Ramkumar et al, 2018) who reported protease stability at 50 ℃. This contrasts with Naidu (2011) who reported a reduction in protease activity beyond 35 ℃.…”
Section: Isolation Of Proteolytic Bacteriasupporting
confidence: 94%
See 2 more Smart Citations
“…Bacillus ruris protease had its highest activity at 50 ℃ (100%), while further temperature rise resulted in reduced protease activity decreasing to 77.042 % at 70 ℃. This result agrees with reports by (Adinarayana et al, 2003;Giri et al, 2011;Jayashree et al ., 2014;Niyonzima and More, 2014;Ramkumar et al, 2018) who reported protease stability at 50 ℃. This contrasts with Naidu (2011) who reported a reduction in protease activity beyond 35 ℃.…”
Section: Isolation Of Proteolytic Bacteriasupporting
confidence: 94%
“…Findings from this study showed that surfactants such as tween 20, triton X, (SLS), (SDS), enhanced the protease activity of Bacillus ruris, while inhibitors such as 2-mercaptoethanol (BME), dithiothreitol (DTT), and ethylenediaminetetraacetic acid (EDTA) had varying inhibitory effects on Bacillus ruris protease as shown in Figure 7. This result is similar to reports obtained by Jayashree et al (2014) who reported improvement of protease activity by tween 20 and triton X and minimal effects of the oxidizing agents on protease enzyme. Further studies on enzyme inhibition could offer more insights regarding the nature of the proteases, its cofactor requirements and its active center (Jayashree et al, 2014).…”
Section: Isolation Of Proteolytic Bacteriasupporting
confidence: 92%
See 1 more Smart Citation
“…The enzyme inactivated by TCA was used as the control. The amount of enzyme liberating 1µg of tyrosine per ml for 30 minutes at 37°C corresponds to one unit of protease activity (U) (Jayashree et al, 2014). Lowry's method was used in estimating protein concentration where Bovine serum albumin (BSA) was the standard (1951).…”
Section: H Quantitative Screening For Protease Enzymementioning
confidence: 99%
“…After incubation, culture was harvested by centrifugation at 10,000 rpm for 10 min at 4℃. The cell free supernatant was used as the enzyme source for protease assay and the protease activity was determined as described by Jayashree et al [ 12 ]. One milliliter of enzyme solution was added to 1 mL 2% (w/v) casein solution (dissolved in 50mM phosphate buffer with pH 7) and incubated in water bath at 37℃ for 20 min.…”
Section: Methodsmentioning
confidence: 99%